Multiple intelligence based e-books - Shiratuddin, Norshuhada; Landoni, Monica (researchgate, 2001)
This paper describes a study on the design of teaching-learning materials and the use of technology in school environment.One essential component of this study is the definition of models on how electronic textbooks (e-books), one of the fundamental tools in the school recently, should be designed to be practiced. We postulate that a crucial feature for children e-books would be to present contents by mixing different presentation modes (graphic page, talking page, hypermedia page and web page modes) and including various activities in each mode which support and nurture as many children’s intelligences and learning styles as possible